High injury rates and weak injury prevention strategies in football referees at all levels of play. (2nd November 2021) - Szymski, Dominik; Opitz, Sabine; Pfeifer, Christian; Rupp, Markus; Angele, Peter; Alt, Volker; Krutsch, Werner; Krutsch, Volker
Abstract : Football referees need other physiological requirements on field than football players and are affected by different types of injury. The absence of referees may result in canceled matches, so special focus should be placed on injury prevention through specific training programs for referees. This study retrospectively analyzed injury occurrence and prevention strategies for German football referees at the different levels of play over one season. Data were collected by means of seasonal injury reports based on the consensus statement of injury definition and data collection. Of the 923 participating referees, 91 (9.9%) played at the professional level, 151 (16.3%) at the semi‐professional, and 681 (73.8%) at the amateur level. 86.2% ( n  = 796) were men and 13.8% ( n  = 127) women. Referees at the amateur level showed the highest injury incidence (3.14/1000 h football) compared to referees at the semi‐professional (1.92/1000 h; p  < 0.001) and professional level (1.01/1000 h; p  < 0.001). Most referees at the amateur ( n  = 372; 56.4%) and semi‐professional level ( n  = 46; 31.3%) conducted warm‐up programs of <10 min, whereas the mean warm‐up duration of professional referees was >11 min ( n  = 75; 82.4%). Although running and stretching exercises were common among referees during warm‐up, preventive exercises focusing on coordination and trunk muscles were less frequent, especially among amateur referees (jumping: 15.9%; strengthening: 9.7%; balance exercises: 7.9%). Injury incidence was highest at lower amateur levels, which thus has specific need for injury prevention. Appropriate training exercises to prevent injuries of referees were weak at all levels of play, especially the lack of strength, plyometric, and balance exercises in training and warm‐up programs.